Homossexualidade e velhice: os processos de subjetividade da sexualidade em homossexuais idosos - Lemos, Alex Eduardo [UNESP] (2015)
This dissertation investigates the subjectivity construction toward homosexuality and aging people with ages equal or more than sixty years. As from three interviews that were analyzed the life's subjectivity process these participants, focusing expressions come out of the closet and reports' subjectivity construction in homosexual context. Based on the theoretical contribution of socio historic perspective and human development, arise the reflection about sexuality and aging in the social environment, this research reflects about the conception from those individuals, experience (living; feeling), memories and experiences that mark this generation, the affective linkages, the daily activities and the homoaffectives practices. Before stigma of being homosexual and aged, it examines as the relational experiences are and what the perspectives built by those peoples and identify the production of new subjectivity about the way to experience this stage of life. There is an urgency to work the society and, specifically, the health professional, to broaden the concept of sexuality and not reduce it to the sexual act itself, it being part, and not the whole concept. The study provided an opportunity to see that is common homosexuals suffer exclusion on nowadays, as the media shows daily, showing that many are, including, subjected to constraints at the time they expose their identity in certain places, or in the presence of certain groups, reaching some suffering even, physical attack, and we see this exclusion is intensified in cases of homosexuals who take more positions associated with the feminine, assuming a discordant genre with their sex